Role of School Chairman Leader Ship in Implementing School Based Management in Fundamental Schools 20 Air Kumbang - Sungkono; Harapan, Edi; Wardiah, Dessy (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The principal as a leader in the school environment is not only obliged to carry out administrative duties but also concerns the task of how to manage all school programs. He must be able to lead and direct both administrative aspects and the educational process in his school. This study aims to determine and describe the role of principal leadership in implementing school-based management at SD Negeri 20 Air Kumbang. The method used is a qualitative method. Data collection techniques using observation, interviews and documentation. The results of this study can be concluded that the leadership of the principal at SD Negeri 20 Air Kumbang has fulfilled the characteristics as a principal by being able to lead his subordinates well, the principal is able to empower the school's resources in the school and the principal of SD Negeri 20 Air Kumbang has a very important role important in the successful implementation of SBM, especially in the areas of financial management and public relations management. The principal tries to implement SBM effectively and efficiently so that school goals can be fulfilled.